Changes in moorland and heathland bird abundance in southwest England in relation to environmental change. Issue 4 (1st October 2016) - Sim, Innes M.W.; Stanbury, Andrew J.; Tománková, Irena; Douglas, David J.T.
ABSTRACT: Capsule: Population changes of many moorland and heathland birds in southwest England show associations with environmental change, and the area supports notable breeding populations of species of conservation concern. Aims: To quantify changes in moorland and heathland breeding bird abundance in relation to changes in environmental variables. Methods: A two-visit moorland bird survey method was used to estimate the abundance of 23 target bird species in 2008 and 2014 in Exmoor National Park, southwest England. Data on changes in 25 environmental variables over the same period were used to test associations between changes in bird abundance and environmental change. Results: Fourteen species increased in abundance and nine decreased. Breeding species which wintered on or close to Exmoor were less likely to show negative population changes than species which migrated to winter in southern Europe or Africa. Change in abundance of 18 species was associated with change in at least one environmental variable, and these relationships were broadly consistent with the known ecology of these species. Conclusion: Although some moorland species have declined or gone locally extinct, this area of moorland and heathland in southwest England remains an important stronghold for several species of high conservation concern. The maintenance of semi-natural moorland and heathland habitats in areas such as Exmoor may provide important refuges for such species, both now and in the future.